Prevalence of Diabetes in South Asian Countries with special reference to India - Singh, Parmendra Narayan; Yadava, R. S. (National Geographical Journal of India, 2022)
Diabetes is one of the non-communicable chronic diseases which is generally characterized by high blood glucose level and its associated complications like hypertension, renal failure and blindness. With largest number of diabetes patients in the world, India is earning the dubious distinction of being termed as the “Diabetes capital of the World”. The present paper focuses on the spatial pattern of incidences of diabetes in Indiaas compared to top ten diabetic nationsincluding south Asian nations. In addition to this, paper also focuses on the relationship between socio-economic factors and self-reported cases of diabetes. We have attempted to explore the geographical variation in the prevalence of diabetes between different states of India. In this paper researchers have made an attempted to reveal the association between obesity and self-reported diabetes in the different states of India. The analysis is based on data published by National Family Health Survey-III. The result shows that older age group, male, higher educated and wealthy people appear to be at greatest risk for diabetes. The data also reflects the substantial geographical controls in diabetes prevalence. The study is having its strength due to the fact of large nationally representative survey to assess the socio-economic condition of patient and conspicuous pattern of this disease